Effects of botanical extracts and antibiotic on incidence and severity of bacterial blight of cotton incited by Xanthomonas axonopodis pv. Malvacearum - Iliya Bawa; H. Nahunnaro; Luka Yelwa Barde; Tabita Sule Gaba; Alhaji Musa (Future Science, 2021)
A multilocational field trial was conducted to investigate the effect of some plant extracts (Bolanite aegyptica, Eucalyptus camaldulensis and Citrus aurantium) and a synthetic antibiotic (Streptomycin) on the incidence and severity of angular leaf spot on five cotton genotypes namely SAMCOT-8, SAMCOT-9, SAMCOT-10, SAMCOT-11 and SAMCOT-12 in Yola and Jalingo, both located in the northern guinea savannah zone of Nigeria. The experiment was carried out on a split-plot design having three replications with cotton genotypes on the main plots and plant extracts on the sub-plots. Data collected on the incidence and severity of the disease were analysed using the Generalized Linear Model procedure and means separation at 5% level of probability by Duncan Multiple Range Test. Findings of the study revealed that Streptomycin and Bolanite aegyptiaca were able to reduce the disease incidence by 18.12% from 58.69% in Yola at 13 WAS. In Jalingo however, B. aegyptiaca was found to have reduced the disease severity from 52.12% to 19.69% at 13 WAS. SAMCOT-8 consistently recorded lower incidence and severity means in Yola and Jalingo of 47.96%; 59.12% and 40.82%; 39.70% while SAMCOT-12 recorded higher means of 53.29%; 59.82% and 48.03%; 46.70% respectively.